A Population Pharmacokinetic/Pharmacodynamic Model Predicts Favorable HDL Cholesterol Changes Over the First 5 Years in Children Treated With Current Efavirenz-Based Regimens - Nontiya Homkham (2018)
© 2016, The American College of Clinical Pharmacology Efavirenz use is associated with changes in cholesterol concentrations, but it is unclear whether this effect is related to drug concentrations. Using efavirenz and cholesterol plasma concentrations measured in 87 antiretroviral-naive children in Thailand, we assessed indirect response models to describe the evolution of high- and low-density lipoprotein (HDL, LDL) cholesterol concentrations in relation to efavirenz plasma concentrations over time where efavirenz was assumed to either stimulate cholesterol production or inhibit its elimination. Simulations of cholesterol evolution for children with different average efavirenz concentrations (Cav) according to their assumed status of “fast” or “slow” metabolizers of efavirenz were performed. At treatment initiation, children's median (interquartile range, IQR) age was 8 years (5 to 10), body mass index z-score 0.01 (–1.05 to 1.44), HDL 31 mg/dL (24 to 44), and LDL 83 mg/dL (69 to 100). Median (IQR) efavirenz Cavwas 1.7 mg/L (1.3 to 2.1) during the period of observation. The best model describing the evolution of HDL and LDL cholesterol concentrations over time assumed that efavirenz inhibited their elimination. HDL concentrations increase over 5 years, whereas LDL concentrations increased only during the first 4 months and then returned to baseline levels afterward. Simulations predicted that, after 3 years, HDL would increase to 63 mg/dL in “fast” metabolizers and 97 mg/dL in “slow” metabolizers of efavirenz. The population pharmacokinetic-pharmacodynamic (PK-PD) model shows that favorable HDL cholesterol changes can be expected in children with current efavirenz dosing guidelines over 5 years of treatment.